AQM – The Austrian Quarterly Model of the Oesterreichische Nationalbank - Gerhard Fenz; Martin Spitzer (Oesterreichische Nationalbank (OeNB), 2005)
The modelling strategy of the Austrian Quarterly Model (AQM) is in the tradition of the "neoclassical synthesis", a combination of Keynesian short-run analysis and neoclassical long-run analysis. The short run dynamics are based on empirical evidence, the long run relationships are derived from a neoclassical optimization framework. Adjustment processes to the real equilibrium are sluggish. Imperfections on goods and labour markets typically prevent the economy to adjust instantaneously to the long run equilibrium. In the current version of the AQM the formation of expectations is strictly backward looking. The relatively small scale of the model keeps the structure simple enough for projection and simulation purposes while incorporating a suffciently detailed structure to capture the main characteristics of the Austrian economy. The main behavioural equations are estimated using the two-step Engle-Granger technique. The AQM constitutes the Austrian block of the ESCB multi-country model (MCM).
Keywords: 330